NLRP3 Inflammasome Expression in Gingival Crevicular Fluid of Patients with Periodontitis and Chronic Hepatitis C. (19th November 2021) - Surlin, Petra; Lazar, Luminita; Sincar, Cerasella; Gheorghe, Dorin Nicolae; Popescu, Dora Maria; Boldeanu, Virgil Mihail; Pitru, Allma; Florescu, Cristina; Rogoveanu, Ion
Abstract : The study is aimed at assessing the impact that periodontal disease and chronic hepatitis C could have on gingival crevicular fluid levels of the NLRP3 inflammasome, caspase-1 (CASP-1), and interleukin-18 (IL-18) and at evaluating whether the increased local inflammatory reaction with clinical periodontal consequences is correlated to their upregulation. Patients were divided into four groups, according to their periodontal status and previously diagnosed hepatitis C, as follows: (i) CHC group, chronic hepatitis C patients; (ii) P group, periodontal disease patients, systemically healthy; (iii) CHC + P group, patients suffering from both conditions; and (iv) H group, systemically and periodontally healthy controls. Gingival crevicular samples were collected for quantitative analysis of the NLRP3 inflammasome, CASP-1, and IL-18. CHC + P patients expressed the worse periodontal status and the highest NLRP3, CASP-1, and IL-18 levels, the difference being statistically significant (p < 0.05 ). The P group patients also expressed significantly more elevated NLRP3, CASP-1, and IL-18 levels, as compared to nonperiodontal patients (CHC and H groups). Chronic hepatitis C and periodontal disease could have a significant influence on the upregulation of NLRP3 inflammasome and its components, possibly contributing to an increased local inflammatory reaction and clinical periodontal consequences.